Identification, Knowledge Engineering and Digital Modeling for Adaptive and Intelligent Control - Bakhtadze, Natalia; Yadykin, Igor; Torgashov, Andrei; Korgin, Nikolay (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue aimed to bring together scientists working in various branches of control theory to discuss manufacturing control problems that include the following: enterprise control and digital ecosystem creation; the development of identification theory and methodology, and related mathematical problems; parameter, nonparametric, and structure identification and expert analysis; problems regarding selection and data analysis; control systems with an identifier; modeling in intelligent systems; simulation procedures and software; digital identification; reinforcement learning; quantum modeling; intelligent model predictive control; predictive cognitive issues; problems with software quality for complex systems; and global network resources for support processes of modeling and control.